The Second World War, Vol. 3 - Grove, Philip D. (Essential Histories, 2003)
This volume provides a comprehensive guide to three major theaters of combat: the Atlantic, the Mediterranean, and the Indian Ocean. The war at sea was a critical contest, as sea-lanes provided the logistical arteries for British and subsequent Allied armies fighting on the three continents of Africa, Asia, and Europe. Land forces ultimately won World War II, but the battles at sea fundamentally altered the balance of military power on the ground.